Respon Pertumbuhan Dan Hasil Jamur Merang (Volvariella volvaceae) Akibat Penambahan Berbagai Konsentrasi Pupuk Organik Cair Dan Air Kelapa Yang Berbeda - Neneng Farida Solihat; Ani Lestari; Tatang Surjana (Peneliti.net, 2021)
The experiment was carried out in kumbung mushroom, Gadog Village, Tamelang Village, Purwasari District, Karawang Regency, West Java Province from May to June 2021. The experimental method used was a single factor Randomized Block Design (RBD) with 4 replications. There were 7 treatments, namely A (Control without treatment), B (LOF 30 ml), C (LOF 40 ml), D (LOF 50 ml), E (Coconut Water 250 ml), F (Coconut Water 350 ml), and G (Coconut Water 450 ml). If the data were analyzed by means of variance and the F test at 5% level showed significant results, then the Duncan Multiple Range Test (DMRT) test at 5% level was carried out to determine the best treatment. The results showed that the response was not significantly different from the application of liquid organic fertilizer nutrition and coconut water nutrition to all treatment parameters. The highest average fruit body length was found in treatment G (450 ml Coconut Water) which was 3,30 cm and was not significantly different from the others.